2007
DOI: 10.1071/ea06290
|View full text |Cite
|
Sign up to set email alerts
|

The relationship of lamb growth from birth to weaning and the milk production of their primiparous crossbred dams

Abstract: The growth rate of 667 single cross lambs from birth to 4 weeks (Period 1) and 4 weeks to weaning at 12 weeks (Period 2) was measured, along with the milk production of their 520 primiparous crossbred ewe dams over 3 years. The lambs were the progeny of Poll Dorset rams and first cross ewes lambing for the first time at 12 and 19 months of age. The first cross ewes were the progeny of Merino ewes mated to 30 individual sires from several maternal sire breeds, including Border Leicester, East Friesian, Finnshee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
11
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 12 publications
3
11
1
Order By: Relevance
“…The greater estimated milk production observed from ewes offered the 120% ME treatment (McGovern et al, 2015) is reflected in increased growth rates from their offspring during the first 3 wk of life. Similar to observations made in the current study, greater milk yields in early lactation have been previously shown to give lambs a weight advantage that remains present up until weaning (Morgan et al, 2007). In contrast, lambs born to ewes that received the 80% ME treatment were disadvantaged by reduced milk yields in early lactation but had the potential to achieve growth rates equivalent to their counterparts from wk 4 until weaning.…”
Section: Discussionsupporting
confidence: 70%
See 2 more Smart Citations
“…The greater estimated milk production observed from ewes offered the 120% ME treatment (McGovern et al, 2015) is reflected in increased growth rates from their offspring during the first 3 wk of life. Similar to observations made in the current study, greater milk yields in early lactation have been previously shown to give lambs a weight advantage that remains present up until weaning (Morgan et al, 2007). In contrast, lambs born to ewes that received the 80% ME treatment were disadvantaged by reduced milk yields in early lactation but had the potential to achieve growth rates equivalent to their counterparts from wk 4 until weaning.…”
Section: Discussionsupporting
confidence: 70%
“…However, imposing a more severe restriction for a longer interval before or during gestation may have more profound effects on maternal behavior, as seen in studies performed by Dwyer et al (2003) and Hernandez et al (2010). The ability of the ewe to produce milk is a key driver of early lamb growth and, ultimately, survival (Morgan et al, 2007;Tygesen et al, 2008). The strong correlation identified between lamb growth rate and ewe milk production (Snowder and Glimp, 1991) allowed for the estimation of milk yield in the present study, using an equation as determined by Robinson et al (1969).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…The differences in ewe liveweight between treatment groups, and the lack of differences in lamb birthweight, suggests that nutrients may have been partitioned towards the ewes for mammary development or to prevent body condition loss rather than fetal growth. This may have a positive effect on milk production in early lactation and on lamb growth from birth to weaning (Morgan et al 2007). Supplementation has been shown to have a positive effect on colostrum let down (Banchero et al 2007), although in this study, where lamb plasma GGT concentrations were used as an indirect measure of colostrum intake, no differences were found.…”
Section: Cm) and Concentrate Supplementation (Yes V No) On Lamb Plascontrasting
confidence: 65%
“…Profitability in the livestock industry is driven by the efficiency of production characteristics such as the growth and development of offspring postpartum (Redmer et al, 2004). The plane of nutrition available to the ewe during gestation has been shown to positively influence both udder development and subsequent lactation performance (Blair et al, 2010), and the ability of the dam to produce milk for her offspring is a key driver of neonatal growth and development (Morgan et al, 2007). Optimal maternal nutrition and subsequent fetal growth, as precursors of efficiency, are therefore critical in determining the profitability of meat and lamb production enterprises (Redmer et al, 2004).…”
Section: Introductionmentioning
confidence: 99%